MiRNA-155 silencing reduces sciatic nerve injury in diabetic peripheral neuropathy. (October 2019) - Chen, Ji; Li, Chao; Liu, Wenjie; Yan, Bin; Hu, Xiaoling; Yang, Fengrui
Abstract : Neuropathic pain represents one of the most common complications associated with diabetes mellitus (DM) that impacts quality of life. Accumulating studies have highlighted the involvement of miRNAs in DM. Thus, the current study aimed to investigate the roles of miR-155 in diabetic peripheral neuropathy (DPN). In vitro DPN models were established using rat Schwann cells (SCs) by treatment with 5.5 mM glucose. Gain- or loss-of-function studies were conducted to determine the effect of miR-155 on Nrf2, cellular function, reactive oxygen species and inflammation. Rat DNP models were established by streptozotocin injection and damage of sciatic nerve. Next, miR-155 antagomir or agomir was employed to investigate the effects associated with miR-155 on motor and sciatic nerve conduction velocity (MNCV, SNCV), angiogenesis and inflammatory response in vivo . Nrf2 was identified to be a target of miR-155 by dual-luciferase reporter gene assay. Silencing of miR-155 or restoration of Nrf2 promoted cell proliferation, inhibited apoptosis and alleviated inflammation in vitro . miR-155 antagomir-induced inhibition increased MNCV and SNCV, strengthened angiogenesis and alleviated inflammation in DPN rats. Additionally, the effects exerted by miR-155 were reversed when Nrf2 was restored both in vitro and in vivo . Taken together, the key findings of our study provide evidence indicating that miR-155 targeted and suppressed Nrf2 in DPN. miR-155 silencing was found to alleviate sciatic nerve injury in DPN, highlighting its potential as a therapeutic target for DPN.